2003
DOI: 10.1021/jo035087w
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Evaluation of Intramolecular Electron Transfer Reactions in Halobenzenes and Stabilized Derivatives

Abstract: The potential energy surfaces for the fragmentation of the radical anions of p-nitrochlorobenzene and p- and m-chloroacetophenones were explored using first principle methods. The behavior of these compounds, stabilized by pi acceptors, is compared to that shown by the unsubstituted halobenzenes (PhX, X = F, Cl, Br, I). The presence of pi and sigma radical anions was inspected as well as the intramolecular electron transfer (intra-ET) from the pi to the sigma surface, responsible for the dissociation of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 76 publications
4
60
0
Order By: Relevance
“…Furthermore, prior to the bond breaking the π-SOMO is transformed into a σ -SOMO, which is mainly localized at the C-Cl bond, cf. phase as well as in polar solvents, which is obviously important at least for the final formation of the free chloride anion [24]. Their results agree with the experimentally observed reactivities.…”
Section: Quantum Chemical Calculationssupporting
confidence: 89%
“…Furthermore, prior to the bond breaking the π-SOMO is transformed into a σ -SOMO, which is mainly localized at the C-Cl bond, cf. phase as well as in polar solvents, which is obviously important at least for the final formation of the free chloride anion [24]. Their results agree with the experimentally observed reactivities.…”
Section: Quantum Chemical Calculationssupporting
confidence: 89%
“…The role of the π* orbital energy becomes well evident by a close examination of both the chloride and bromide series. The trends of π* energies are 5a < 6a for the chlorides and 8 < 5b < 6b for the bromides [39,40]. This trend is exactly the opposite of that found for the α values.…”
Section: Aromatic Halidesmentioning
confidence: 60%
“…In the same context, detailed studies have been carried out on the role of single factors modulating the process, such as the reactant molecular structure (organic moiety and halide leaving group), the nature, morphology and state of the electrode surface [29], the adsorption of the reagents and products [30,31], and the role of the supporting electrolyte [32], while few preliminary studies have been reported concerning the role of the solvent [33][34][35], and a more systematic investigation is still overdue.…”
Section: Introductionmentioning
confidence: 99%
“…This modulation can be huge and is typically asymmetric for DET processes, since a polar solvent, like acetonitrile, will preferentially stabilize the species having the highest charge density, such as the halide anions resulting from the process; thus solvation affects both the process thermodynamics and kinetics [35]. At the same time the solvent also affects the rate of mass transfer (through its viscosity) and the extent and mode of specific adsorption processes.…”
Section: Introductionmentioning
confidence: 99%